The Growing Threat of Ransomware What Accountants, Their Clients, and Security Professionals Need to Know - Ryle, Patrick; Hicks, Robin; Shemroske, Kenneth; McKnight, Mark; Bueltel, Brett (The Journal of Accounting and Management, 2023)
Objectives This paper is designed to prepare accountants to meet the dangerous challenges posed by ransomware. Prior Work Business operating conditions concerning ransomware have never been more dangerous. In confronting these dangers, prevailing data protection regimes have proven frighteningly inadequate. This paper explores ransomware’s potential impact, and the institutional, organizational, and cultural approaches necessary in the preparation and prevention of such attacks. Approach This paper presents a review of the development of the threat of ransomware outlines several steps accountants can take to prevent such incidents from occurring, and outlines steps accountants can take after a security failure in the face of a ransomware attack. This paper highlights the importance of devoted preparedness., Results This paper implores accountants to take the threat of ransomware seriously, to understand that cyber-attacks are unpredictable and that the time to prepare is now. Implications We examine post-incident mitigation considerations and the ongoing organizational, professional, reputational, and financial consequences of a successful ransomware attack. Value This paper’s contribution provides an examination of ransomware awareness, steps that must be taken in preparation, and the costs of failure in a context unique to accounting and tax professionals.